Tanggung Jawab Ayah Terhadap Biaya Pemeliharaan Anak Setelah Suami Mengucapkan Ikrar Talak - Elsa Aulia Dewi (UNIB Press, 2021)
Married life does not always run happily and eternally based on the One Godhead as stated in Law No.1 of 1974 concerning Marriage, which will eventually lead to divorce. Divorce can be pursued if it meets the reasons that have been regulated by statutory regulations. Divorce has an impact on fathers, mothers and children, the child is the main concern for this impact because the survival of the child after divorce is still the responsibility of parents, especially fathers, for the cost of maintaining and educating the child. This study aims to look at the judges' considerations in determining the costs of the father's responsibility after divorce and in what form the father's responsibility for the cost of maintaining and educating the child. This type of research is a normative juridical research method using literature. The results of the study concluded that there were still many parents, especially fathers who gave up their responsibilities after divorcing, with this the court decision punished and binded parents, namely fathers to continue to provide for their children, because divorce resulted in separation between husband and wife even between husbands (fathers). with the child and the wife (mother) with the child, avoiding neglecting the child's life, the court judge decides the father's responsibility for the cost of caring for the child after the divorce.